Conceptual Analysis Of Lean Principles And Tools In Manufacturing Industries - Osman, Muhamad Nazmi (Universiti Sains Malaysia, 2022)
Today, the ideas and techniques of Lean Manufacturing (LM) are utilised extensively by companies all over the world to reduce waste and make processes more effective. The Lean methodology is widely acknowledged as one of the most effective methods for boosting an organization's productivity and, by extension, its level of competitiveness. The purpose of this paper is to find the implementation status of Lean principles and tools across Malaysian manufacturing organizations through the empirical survey methodology. This paper provides a discussion of lean ideas and techniques that have been implemented in the Malaysian industries involved in manufacturing. The survey questionnaire was developed based upon literature review conducted on LM and also considered experts suggestion in the field of LM. The survey questionnaire was sent to 120 respondents that are currently working in manufacturing industries located in Malaysia. The selected respondents were production managers, quality managers, sales managers, maintenance managers, and also engineering students. The empirical survey collected 107 filled survey questionnaires from Malaysian manufacturing industries. This study makes a contribution by highlighting the relationship of applying lean tools to lean principles within the context of the Malaysian manufacturing sector. study. In lean manufacturing principles, five primary rules are used to measure leanness. These principles include value, value stream, flow, pull, and perfection. In addition, the analysis illustrates how the five different lean principles connect to the lean tools present in the production system. However, for an organization to successfully implement lean, it must choose the best tools for production. There are many lean tools, such as Value Stream Mapping (VSM), Cellular Manufacturing (CM), U-line System, Line Balancing, Inventory Control, Single Minute Exchange of Dies (SMED), Pull System, and Kanban. Thus, it is quite hard to select the right tool to implement in their company and achieve each principle's goals. In this paper, an effort has been made to determine which tools can be used for each lean principle by collecting a survey and seeing the significance of the company's preparation for implementing the lean manufacturing system.